Seasonal Variation of Electron Densities: NmE and NmF in Low Latitudes over the Ouagadougou Station, Burkina Faso - Kadidia Nonlo Drabo (Current Research Progress in Physical Science Vol. 9, 2025)
This work was undertaken to contribute to a better understanding of the atmospheric layer by analyzing variations in ionospheric parameters, in particular, the electron density at Ouagadougou station at low latitude during the solar cycle 23. This variation is the result of the disturbances that are regularly observed in the ionosphere, which is the upper part of the Earth’s atmosphere ionized by solar radiation. To do this, we used the IRI (International Reference Ionosphere) in its 2016 version, which is an empirical model that was used to extract data for the days of the months characteristic of the minimum and maximum phases of the solar cycle. We found that the variability of the electron density of the F (NmF) layer and the variability of the electron density of the E (NmE) layer, follow the evolution of sunlight intensity due to the geographical situation close to the ionospheric equator of our study station. NmE and NmF present significant values during the day because the ionization produced by the sun’s rays is important. At the limit of the E and F layers, the ionospheric day corresponds to the period where the NmE and NmF values are important and conversely, during the ionospheric night, the values of NmE and NmF are very insignificant.